A Methodology to Develop a Mobile Application Model to Appraise Housing Design Quality - Chohan, Afaq Hyder; Mohd Affandi, Haryanti; Awad, Jihad; Che-Ani, Adi Irfan (International Journal of Interactive Mobile Technologies (iJIM), 2017)
The variety of planning and design solutions occasionally turns into an underpinning factor for the defects and maintenance issues in built forms. Defects and maintenance that emerges from deficient design indicate that the design has not been conceded in the perception of quality. Reviewing the nature of deficient designs and resulting maintenance problems in various types of built forms revealed that housing sector is most effective of this phenomenon. The reason could be set as; housing planning, design, and construction are a most practiced activity to address the living needs of the ever-growing world population. This research considered that design quality of housing is severely affected in developing countries. In this regard housing standards and bylaws plays a minor role to ensure the housing quality in developing regions. However, it is notable that, in developing regions, the majority of populations have easy access to mobile communication technology. Therefore, it is possible to use mobile technology to educate the people about quality issues of housing and to help them to evaluate the quality of proposed or existing housing. At present, the use of mobile technology has not only heightened the need for IT knowledge but also extend the capabilities of many designers/architects and builders. Hence, there is a niche to develop an integrated hub that could appraise the function of each professional involved in housing processes. This research has established a criterion that, the mobile technology can help common people to understand the quality of house/housing and to ascertain it. The results of the research have surfaced a model of mobile application that could be used later to prepare the real-time mobile application to work as a “design quality assessment tool.”